Uzņēmuma SIA “Orkla Latvija” organizācijas kultūras vadīšana un pilnveide. - Groskaufmane, Simona (Latvijas Universitāte, 2023)
Bakalaura darba tēma ir “Uzņēmuma SIA “Orkla Latvija” organizācijas kultūras vadīšana un pilnveide”. Darba mērķis ir novērtēt uzņēmuma SIA “Orkla Latvija” organizācijas kultūru un sniegt priekšlikumus tās pilnveidei. Bakalaura darba pētījuma rezultātā tika raksturota uzņēmuma SIA “Orkla Latvija” esošā organizācijas kultūra un vēlamā organizācijas kultūra. Bakalaura darba apjoms ir 61 lpp., sastāv no trīs nodaļām – organizācijas kultūras noteicošie faktori, SIA “Orkla Latvija” darbības raksturojums un Organizācijas kultūras novērtējums uzņēmumā – pētījums. Tas satur 1 tabulu, 16 attēlus un 2 pielikumus. Darbā izstrādē izmantoti 49 literatūras avoti.

The theme of this bachelor's paper is Management and development of organizational culture in the company SIA “Orkla Latvija”. The aim of the work is to evaluate the factors determining the organizational culture of SIA "Orkla Latvija" and to provide suggestions for its improvement. As a result of the research of the bachelor thesis, the existing organizational culture and the desired organizational culture of the company SIA "Orkla Latvija" were characterized. The volume of the bachelor's work is 61 pages, it consists of three chapters - the determining factors of the organizational culture, the description of the operation of SIA "Orkla Latvija" and the evaluation of the organizational culture in the company - a study. It contains 1 table, 16 figures and 2 appendices. 49 literature sources were used in the development of the work.
Management and development of organizational culture in the company SIA “Orkla Latvija.
Keywords: Ekonomika un uzņēmējdarbība; Organizācijas kultūra; Uzņēmējdarbība; Vērtības; OCAI; Orkla Latvija